Pengaruh Periode Perputaran Persediaan dan Pertumbuhan Penjualan terhadap Profitabilitas pada CV Dian Ayu Setiabudi Brebes - Bambang Kuryanto; Maftukhin; Hilda Kumala Wulandari; Dumadi; Nur Afridah (Universitas Muhadi Setiabudi, 2021)
Profitability is an important part for every company because the amount or not of profitability obtained will affect the company's financial condition. In addition, inventory turnover is also an important part of the company if the company is able to increase inventory turnover properly which will increase profitability quickly. Sales turnover is also an important thing for companies that affect profitability. If sales increase, then profitability will also increase. The purpose of this study was to determine the effect of inventory turnover, and sales growth on profitability in the company CV Dian Ayu Setiabudi. The type of research used in this study is a type of quantitative research data, which is carried out by processing data with the help of the SPSS application. The data is presented in the form of a table presented in the study and concludes the results of research related to the effect of inventory turnover and sales growth on profitability on CV Dian Ayu Setiabudi. The results of this study show that partial inventory turnover has a significant influence on profitability, partial sales growth has a significant influence on profitability, periods of turnover and sales growth simultaneously have a significant positive effect on profitability.